POINTS OF LINGUISTIC STUDIES AND LANGUAGE TEACHING PERTINENT TO ISLAMIC VALUES - Milal, A. Dzo'ul; Swasono, Endratno Pilih (University of Darussalam Gontor, 2023)
Purpose: This paper reveals the points of linguistic studies and that of language teaching which are relevant to Islamic values. Introduction: Interdisciplinary discussions on linguistic underpinnings including functional linguistics and language teaching principles, and Islamic perspectives have insufficiently been explored. Hence, the study focusing on such a relation gains significance. Method: Using an exploratory descriptive method, the data of this study were collected by exploring the linguistic axioms and language instructional principles which are relevant to Islamic knowledge conveyed in Qur’anic verses and Hadits. Having been collected, they were analyzed by thematic scrutiny, described, and concluded. The findings show that the linguistic points that are associated with Islamic values are the Divine source of language origin, the endowment of language acquisition devices, the compliance with maxims of quality and quantity in cooperative principles, that of politeness rules, and the existence of language variants. Conclusion: Concerning language teaching, the ideas that are appropriate to Islamic values include the importance of communicativeness and collaboration, the comprehensibility of instructional language, content-bound materials, and effective and efficient strategies.